X-ray crystallographic diffraction study by whole powder pattern fitting (WPPF) method: Refinement of crystalline nanostructure polymorphs TiO2 - Md. Ashraful Alam; Shanawaz Ahmed; Raton Kumar Bishwas; Sabrina Mostofa; Shirin Akter Jahan (South African Journal of Chemical Engineering)
High crystalline preferred oriented low strain anatase utilizing a novel and unique approach employing the powder X-ray diffraction (XRD) technique is the prime focus of the investigation. This process effectively enhanced controlled crystalline phase growth with 86.70 % anatase and 13.30 % rutile confirmed through Rietveld refinement in the WPPF method. The prominent crystalline phase providing insights into lattice parameters a = b = 3.7882 Å, c = 9.5143 Å, α=β=γ= 90.0° where lattice strain 0.280 %, lattice volume 136.533 Å3, specific surface area 84.69 m2/g, dislocation density 2.94 × 10–3 nm−2, morphology index 0.722, preference growth -0.087 and packing efficiency 70.13 %. The most intense diffraction was attributed to the (101) plane at 2θ= 25.288° The average crystallite size through various models was 18.45 nm (Scherrer equation), 34.08 nm (Williamson-Hall plot), 22.12 nm (Monshi-Scherrer model), 18.49 nm (Sahadat-Scherrer model), 22.44 nm (Size-strain plot model) and 17.87 nm (Halder-Wagner model) confirming the formation of nano-sized anatase phase of titanium dioxide nanoparticles. The standard powder nanocrystals exhibit a crystallinity of 67.87 %, underscoring the efficacy of the highly oriented anatase with desirable structural and diffraction properties. `This reduction in crystal structure defects and strain, alongside a smaller lattice volume improved stability and high crystalline anatase predominant (101) was observed at low temperatures.